Does open data tell us everything? - Sarli, Leopoldo; Monaco, Federico (Acta Biomedica Atenei Parmensis, 2021)
The community of the entire planet is still grappling with the management of the Sars-CoV-19 pandemic and in some countries the spread of the infection is as serious as it was in Italy in the first months of 2020. In this issue of the magazine Kalli M et al. describe the situation in Chad.[...]